Powering ahead: how UK industry can match Europe's environmental leaders (London, 2016)
"This report will explore the recent history of sustainable industrial policies. There was not one single moment when the threat of global warming stopped being the concern of a committed minority and became widely accepted. However, milestones – such as the success of the Green Party in the UK in elections to the European Parliament in 1999, the Red-Green Coalition in Germany in 2000, the Stern Review of October 2006, which helped shape the thinking of UK governments under first Tony Blair and then Gordon Brown, and the Climate Change Act introduced by Ed Miliband, will briefly be revisited.